The Role of Forensic Accounting and Non-Financial Measurement for the Financial Audit - Mohamad Mahsun; Oluwatoyin Muse Johnson Popoola; Rida Perwita Sari (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
Due to a lack of competency, including knowledge and experience, non-financial measurement skills are now required by auditors in order to prove fraud. As a result, this research aims to identify the gap between the practice requirements and the output of the audit training centre and the role of the forensic accounting curriculum in filling that gap. This research examines the best strategies for establishing competent and reliable auditing practice results. The non-participatory observation data mining method is used in this study. The study discovered that the auditing education and training centre had not taught and did not have a fraud prevention and detection curriculum based on non-financial measurement. As a result, this study recommends that Training Centre develop the audit curriculum in accordance with The International Education Standard. Furthermore, this study suggests that auditing education and training centres involve forensic accounting practitioners in team-teaching, particularly investigative audit topics.